2017
DOI: 10.1111/dgd.12390
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nitric oxide level results in maturation promoting factor destabilization during spontaneous meiotic exit from diplotene arrest in rat cumulus oocytes complexes cultured in vitro

Abstract: Nitric oxides (NO) act as one of the major signal molecules and modulate various cell functions including oocyte meiosis in mammals. The present study was designed to investigate the mechanism of NO action during spontaneous meiotic exit from diplotene arrest (EDA) in rat cumulus oocytes complexes (COCs) cultured in vitro. Diplotene-arrested COCs collected from ovary of immature female rats after 20 IU pregnant mare's serum gonadotropins (PMSG) for 48 h were exposed to various concentrations of NO donor, S-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(83 reference statements)
0
6
1
Order By: Relevance
“…Similar levels of cAMP were also detected in the group of COCs treated with 1.0 mM L-NAME in subsequent hours. These alterations in nucleotide concentrations are different from those observed in rodents (Tiwari and Chaube, 2017). However, we and others (Schwarz et al, 2014;Botigelli et al, 2017;Dubeibe et al, 2017) have also observed the lack of correlation between cGMP and cAMP concentration during meiosis resumption in bovines.…”
Section: Nos Inhibition In Bovine Ivmcontrasting
confidence: 72%
See 2 more Smart Citations
“…Similar levels of cAMP were also detected in the group of COCs treated with 1.0 mM L-NAME in subsequent hours. These alterations in nucleotide concentrations are different from those observed in rodents (Tiwari and Chaube, 2017). However, we and others (Schwarz et al, 2014;Botigelli et al, 2017;Dubeibe et al, 2017) have also observed the lack of correlation between cGMP and cAMP concentration during meiosis resumption in bovines.…”
Section: Nos Inhibition In Bovine Ivmcontrasting
confidence: 72%
“…NO stimulates the production of cGMP via activation of the soluble guanylate cyclase enzyme (Denninger and Marletta, 1999). Therefore, the reduction in NO production associated with the addition of L-NAME may have induced low cGMP synthesis and may represent one of the possible pathways for meiotic resumption and progression as described in rodents (Pandey et al, 2010;Tiwari and Chaube, 2017).…”
Section: Nos Inhibition In Bovine Ivmmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 28–30 Studies from our laboratory using NO donor and iNOS inhibitor suggest that the reduction in NO level results in spontaneous EDA in rat COCs cultured in vitro. 49 Our results suggest that the increase of total ROS level (almost two fold increase) was associated with meiotic exit from diplotene, as well as M-II arrest. The increase of ROS, decrease of iNOS, and thereby NO levels after 7 h of hCG surge could be due to increased cell proliferation and cellular metabolism within the follicle.…”
Section: Discussionmentioning
confidence: 54%
“…cGMP is produced by the granulosa cells and transported into the oocyte via gap junctions and plays an important role in maintaining meiotic arrest of oocytes 49 . Nitric oxide also inhibits germinal vesicle breakdown (GVBD) in oocytes of preovulatory follicles 50 . Germinal vesicle breakdown (GVB) is the dissolution of the nucleus of an oocyte that is arrested in the prophase of meiosis I, a process that enables the oocyte to resume meiosis.…”
Section: Seeds Ofmentioning
confidence: 99%